Apolipoprotein B in the Risk Assessment, Diagnosis, and Treatment of Cardiometabolic Diseases - Patel, Shaan; Patel, Hina; Mukadam, Shaanali; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2025)
Apolipoprotein B (ApoB) has emerged as a central biomarker and mechanistic driver of atherosclerotic cardiovascular disease (ASCVD), outperforming traditional lipid metrics in both risk stratification and therapeutic targeting. In this article a critical evaluation of the information is presented on the molecular biology, metabolic regulation, and clinical relevance of ApoB isoforms, ApoB100 and ApoB48, which play their own distinct, yet complementary roles in hepatic and intestinal lipid transport. The ways in which ApoB particle density is influenced by insulin resistance, nutrient status, hepatic lipid flux, inflammation, and genetic variation, all of which contribute to dyslipoproteinemic phenotypes associated with ASCVD and metabolic syndrome. Importantly, ApoB levels provide a direct measure atherogenic particle number, offering superior predictive value over low-density lipoprotein cholesterol (LDL-C), particularly in cases of lipid discordance and among statin-treated patients with residual cardiovascular risk. Emerging evidence demonstrates therapies targeting ApoB reduction, including statins, PCSK9 inhibitors, and glucoselowering agents such as GLP-1 receptor agonists, can significantly reduce major adverse cardiovascular events. However, the lipid-modulating effects of agents like SGLT2 inhibitors, metformin, and thiazolidinediones are variable or independent of ApoB changes. The classification of four ApoB-related dyslipoproteinemic phenotypes, normotriglyceridemic hyperApoB, hypertriglyceridemic normoApoB, hypertriglyceridemic hyperApoB, and hyperchylomicronemia, offers a more nuanced approach to cardiovascular risk assessment than LDL-c alone. Collectively, these findings support the integration of ApoB measurement into routine clinical practice as both diagnostic tool and therapeutic target, with the potential to substantially enhance personalized management of cardiometabolic disease.